Area-Wide Management of Fruit Fly Pests - Perez-Staples, Diana; Diaz-Fleischer, Francisco; Montoya, Pablo; Vera, Maria Teresa (Taylor & Francis, 2020)
Fruit fly (Diptera: Tephritidae) pests have a profound impact on horticultural production and economy of many countries. It is fundamental to understand their biology and evaluate methods for their suppression, containment, or eradication. Area-Wide Management of Fruit Fly Pests comprises contributions from scientists from around the world on several species of tephritids working on diverse subjects with a focus on area-wide management of these pests. The first three sections of the book explore aspects of the biology, ecology, physiology, behavior, taxonomy, and morphology of fruit flies. The next two sections provide evidence on the efficacy of attractants, risk assessment, quarantine, and post-harvest control methods. The fifth and sixth sections examine biological control methods such as the Sterile Insect Technique and the use of natural enemies of fruit flies. The seventh section focuses on area-wide integrated pest management and action programs. Finally, the eighth section examines social, economic, and policy issues of action programs aimed at involving the wider community in the control of these pests and facilitate the development of control programs. Features: Presents information on the biology of tephritid flies. Provides knowledge on the use of natural enemies of fruit flies for their biological control. Includes research results on models and diets used for the Sterile Insect Technique. Reports developments on the chemical ecology of fruit flies that contribute to make control methods more specific and efficient. Reviews subjects such as Holistic Pest Management and Area-Wide Management Programs including social, economic, and policy issues in various countries. The Open Access version of this book, available at https://www.taylorfrancis.com/books/9780429355738, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.